Consumption Patterns And Sustainable Fashion In Indonesia: An Analysis Of Attitudes, Intentions, Behaviours And Beliefs Towards The Environment - Panjaitan, Feliks Anggia Binsar Kristian (Indonesian Scientific Publication, 2024)
With an emphasis on consumer attitudes, purchasing intentions, environmental views, and actual consumption behaviors connected to sustainable fashion, this study explores Indonesian consumers' consumption patterns and sustainable fashion practices. Data were gathered via a cross-sectional survey of 248 Indonesian consumers using a quantitative research design. The data was analyzed using Structural Equation Modeling (SEM) and Partial Least Squares (PLS) regression analysis to test the proposed correlations between the variables. The findings show a strong positive correlation between consumer attitudes, intentions to buy, views about the environment, and real consumption practices concerning sustainable fashion. The study revealed that customer attitudes and environmental views are significant indicators of purchase intentions and actual consumption behaviors. This underscores the significance of influencing consumer perceptions and environmental awareness to encourage the adoption of sustainable fashion. Furthermore, it was discovered that buying intentions had a substantial impact on actual consumption habits, highlighting the significance of encouraging purchase intentions to promote the consumption of sustainable fashion. Policymakers, industry stakeholders, and fashion businesses looking to support sustainable fashion practices in Indonesia can all benefit from the study's findings.